Efeito da rotação de culturas sobre a emergência de plântulas, incidência de podridões radiculares e rendimento de grãos de soja - Segalin, Marivane (2007)
Cultural practices have the potential to reduce the incidence of root rot in soybean crop. The goal of the present work was to assess the effects of winter crops (oats, ryegrass, peas, rape and wheat), monoculture, crop rotation and, winter fallow on the incidence of root rots (RR) and grain yield in soybeans. The trials were carried out in the experimental field of Faculdade de Agronomia and Medicina Veterinária, in the 2005/2006 and 2006/2007 growing seasons. A randomized block with four replications was used as experimental design. It was shown that the soil of the experimental field may be considered suppressive to the fungi causing seed rot and seedling blight in soybeans. On the other hand, in the 2005/2006 growing season there was significant effect of ryegrass, peas, rape and wheat in the reduction of RR incidence. In the over all mean there was reduction of RR incidence by soybean rotation with corn. Regarding to grain yield, in the treatment in which soybean was cultivated after two repeated corn crops, was the highest, with 2,161.6 Kg.ha-1 in the 2004/2005 growing season and 3,315.9 Kg.ha-1 in the 2005/2006 season, in comparison with the treatments of soybean cultivated in monoculture yielding 1,963.9 Kg.ha-1 and 2,908.2 Kg.ha-1 respectively, and the treatment of soybean cultivated after one con crop with 1,936.6 Kg.ha-1 and 3,148,0 Kg.ha-1 respectively. There was no statistical difference in relation to the winter crops on the soybean RR incidence. Fusarium spp, Macrophomina phaseolina, Phomopsis sp. e Rhizoctonia solani were the main fungi isolated from the soybean roots